Flame-retardant polyamide material as well as preparation method and application thereof

By adding specific components to the polyamide material and combining polyethylene and polyethylene glycol, the shortcomings of polyamide materials in terms of heat and humidity resistance and baking resistance are solved, and the flame retardant and comprehensive materials are achieved. Performance improvement.

CN119463470AActive Publication Date: 2025-02-18TIANJIN KINGFA NEW MATERIAL +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411536186.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-18
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing polyamide materials have shortcomings in terms of heat and humidity resistance and baking resistance, and cannot meet the high requirements of modern high-tech products for the comprehensive performance of materials.

Method used

By adding brominated polystyrene, antimony-containing flame retardant synergist and compound temperature resistance agent to the polyamide material, specifically, the combination of polyethylene and polyethylene glycol, polyethylene: polyethylene glycol The weight ratio is (1.5-5): 1, combined with the specific viscosity average molecular weight and weight average molecular weight, melt blending modification is carried out.

Benefits of technology

The flame retardant, high temperature resistance, humidity resistance and baking resistance of polyamide materials have been achieved, ensuring that the material can maintain good performance in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flame-retardant polyamide composite material which comprises the following components in parts by weight: 70-80 parts of polyamide; 12 to 30 parts of brominated polystyrene; 5 to 12 parts of an antimony-containing flame retardant synergist; 6-16 parts of a compound temperature resistant agent; the compound temperature-resistant agent is a compound of polyethylene and polyethylene glycol, and the weight ratio of polyethylene to polyethylene glycol is (1.5-5): 1. Through compounding of high-molecular-weight polyethylene and polyethylene glycol, hydroxyl groups of polyethylene glycol can effectively improve the surface activity of polyethylene during melt blending modification, and the polyethylene, polyamide and the whole material system form a stable interface structure, so that the material is effectively prevented from being influenced by an external high-temperature and high-humidity environment; therefore, the material can still keep good performance in a high-temperature and high-humidity environment. Meanwhile, the weight-average molecular weight of brominated polystyrene and polyethylene are in the same order of magnitude, so that the brominated polystyrene has good compatibility, and the bending fracture inhibition performance after high-temperature baking can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a flame retardant polyamide material and a preparation method and application thereof. Background Art

[0002] As an engineering material, polyamide is widely used in various fields. With the continuous improvement of technology, the product types are increasing. However, with the development of modern high technology, the products with durability, friction resistance and complex structural design are gradually increasing, which puts higher requirements on the comprehensive performance of materials. Traditional wear-resistant materials can no longer meet the requirements of the market, and the choice of wear-resistant agents is also limited. Colleagues in the industry have also conducted different related research.

[0003] CN112430391A records the use of ultra-high molecular weight polyethylene as an anti-wear agent and polyethylene glycol as a release agent. However, the patent does not pay attention to heat and moisture resistance and baking resistance.

[0004] CN112552676A records a gas-assisted forming polyamide composite material, including 37-86.7% polyamide resin, 10-40% flat glass fiber, 2-8% impact modifier, 0.5-5% ultra-high molecular weight polyethylene, 0.2-2% polyethylene glycol, 0.1-3% colorant, and 0.5-5% additive. This scheme mainly utilizes polyethylene glycol to form intermolecular hydrogen bonds with polyamide, reduces the crystallization temperature of the composite material, improves the appearance, and the flat glass fiber helps to provide a more isotropic dispersion, which improves the fluidity of the composite material. However, this scheme cannot significantly improve the heat and moisture resistance, and the improvement of the baking resistance is also limited. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical defects and provide a flame retardant, high temperature and moisture resistant, and baking resistant polyamide material, as well as a preparation method and application.

[0006] The present invention is achieved through the following technical solutions: A flame retardant polyamide material, comprising the following components by weight: Polyamide 70-80 parts; 12-30 parts of brominated polystyrene; Contains 5-12 parts of antimony flame retardant synergist; Compound heat resistant agent 6-16 parts; The composite heat-resistant agent is a composite of polyethylene and polyethylene glycol, and the weight ratio of polyethylene to polyethylene glycol is (1.5-5):1; The viscosity average molecular weight of the polyethylene is 400,000-750,000; The weight average molecular weight of the polyethylene glycol is 450-12000; The weight average molecular weight of the brominated polystyrene is 180,000-250,000.

[0007] The testing method for the weight average molecular weight of brominated polystyrene is: using gel permeation chromatography.

[0008] The test method for viscosity average molecular weight of polyethylene is: GB / T1632.3-2010.

[0009] The weight average molecular weight test method of polyethylene glycol is as follows: weigh appropriate amount of polyethylene glycol 600, polyethylene glycol 1000, polyethylene glycol 4000, polyethylene glycol 7000, polyethylene glycol 10000 molecular weight reference substances, dissolve and dilute with mobile phase to make a solution containing about 2 mg per 1 ml as reference substance solution. Weigh appropriate amount of sample, dissolve and dilute with mobile phase to make a solution containing about 2 mg per 1 ml as test solution. Determine according to molecular exclusion chromatography (General Rule 0514), use gel chromatography column with appropriate separation range, 0.1 mol / L sodium nitrate solution (containing 0.02% antibacterial agent) as mobile phase, differential refractive index detector; detector temperature 35°C, column temperature 35°C, take 100 μl of reference substance solution and inject it into liquid chromatograph, record chromatogram, calculate regression equation by GPC software, linear correlation coefficient R should not be less than 0.99. Take 100μl of the test solution and measure it in the same way. Calculate the weight average molecular weight and molecular weight distribution of the test sample according to the regression equation. The weight average molecular weight of the test sample should be 90%-110% of the labeled value, and the distribution coefficient should be 90%-110% of the product labeled value. The antibacterial agent is 2-methyl-4-isothiazoline-3-one and 5-chloro-2-methyl-4-isothiazoline-3-one (such as ProClin300) or other small molecule antibacterial agents with equivalent antibacterial efficacy.

[0010] The weight of the polyamide that can achieve the purpose of the present invention can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts. The weight of the brominated polystyrene can be 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts. The weight of the antimony-containing flame retardant synergist can be 5 parts, 7 parts, 9 parts, 10 parts, 12 parts. The weight of the compounded temperature-resistant agent can be 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts.

[0011] The viscosity-average molecular weight of the polyethylene that can achieve the purpose of the present invention can be 400,000, 420,000, 440,000, 460,000, 480,000, 500,000, 520,000, 540,000, 560,000, 580,000, 600,000, 620,000, 640,000, 660,000, 680,000, 700,000, 720,000, 750,000, etc.

[0012] The weight average molecular weight of the polyethylene glycol that can achieve the purpose of the present invention can be 450, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, etc.

[0013] The weight average molecular weight of the brominated polystyrene that can achieve the purpose of the present invention may be 180,000, 190,000, 200,000, 210,000, 220,000, 230,000, 240,000, 250,000, etc.

[0014] Moreover, in the technical solution of the present invention, the polyamide accounts for no less than 50wt% of the total weight of the flame retardant polyamide material.

[0015] In the present invention, the polyethylene content ranges from 3.6 to 13.3 parts, and the polyethylene glycol content ranges from 1 to 6.4 parts.

[0016] The polyethylene content that can achieve the purpose of the present invention is 3.6 parts, 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts, 10.0 parts, 10.5 parts, 11.0 parts, 11.5 parts, 12.0 parts, 12.5 parts, 13.0 parts, 13.3 parts, etc.

[0017] The polyethylene glycol content that can achieve the purpose of the present invention is 1 part, 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts, 5.0 parts, 5.5 parts, 6.0 parts, 6.4 parts, etc.

[0018] Preferably, the weight ratio of polyethylene:polyethylene glycol is (2.4-3.5):1.

[0019] The weight ratio of polyethylene to polyethylene glycol that can achieve the purpose of the present invention is 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3.0:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, etc.

[0020] The antimony-containing flame retardant synergist is selected from at least one of antimony trioxide and antimony pentoxide.

[0021] Preferably, the weight average molecular weight of the polyethylene glycol is 3800-11000.

[0022] The polyamide resin is selected from at least one of aliphatic polyamide resin, semi-aromatic polyamide resin and polylactamide resin.

[0023] The aliphatic polyamide resin is selected from PA66, PA46, PA610, PA612, PA56, PA510, PA512, PA910, PA912, PA913, PA914, PA915, PA616, PA936, PA1010, PA1012, PA1013, PA1014, PA1210, PA1212, PA1213, PA1214, PA614, PA613, PA615, PA616 and the like.

[0024] The semi-aromatic polyamide is selected from PA MXD6, PA10T, PA10T1010, PA10T66, PA6T, PA6T66, PA9T and the like.

[0025] The polylactam is selected from PA5, PA6, PA11, PA12 and the like.

[0026] It is possible to choose whether to add 0-5 parts of an auxiliary agent according to the actual situation, wherein the auxiliary agent is selected from at least one of a lubricant, a nucleating agent, and an antistatic agent; The preparation method of the flame-retardant polyamide material of the present invention comprises the following steps: uniformly mixing the components according to a proportion, putting them into a twin-screw extruder for melt mixing, extruding and granulating to obtain the flame-retardant polyamide material; wherein the screw length-diameter ratio of the twin-screw extruder is 40-48:1, the barrel temperature is 230-260°C, and the screw speed is 200-550rpm.

[0027] The flame retardant polyamide material of the present invention is used for preparing electronic equipment casing.

[0028] The present invention has the following beneficial effects: The present invention uses polyethylene and polyethylene glycol to compound, and the hydroxyl group of polyethylene glycol can effectively improve the activity of the polyethylene surface during melt blending modification, form a stable interface structure with polyamide and the entire material system, and effectively protect the material from the influence of the external high temperature and high humidity environment, thereby improving the material to maintain good performance after being in a high temperature and high humidity environment. At the same time, polyethylene with a specific viscosity average molecular weight is selected and activated by polyethylene glycol with a specific weight average molecular weight, and has good compatibility with high molecular weight brominated polystyrene, so that the material not only has flame retardant properties, but also obtains good bending properties after high temperature baking. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0030] The sources of raw materials used in the present invention are as follows: PA66: PA66 EPR27, Shenma Group; PA6: PA6 HY-2800A, marine chemical fiber; PA10T: VICNYL 6100P, Zhuhai Wantong Special Engineering Plastics Co., Ltd. PA1010: PA1010 G150, Shandong Guangyin New Materials Co., Ltd.; Brominated polystyrene A: BPS 7010, Shandong Tianyi, weight average molecular weight about 190,000; Brominated polystyrene B: XZ-6700 from Shandong Brothers, weight average molecular weight about 240,000; Brominated polystyrene C: SR-3010 Shandong Xurui, weight average molecular weight about 4,000; Brominated polystyrene D: FR-803P, ICL, weight average molecular weight about 600,000.

[0031] Decabromodiphenylethane: SAYTEX 8010, Albemarle Industries; Brominated epoxy: CXB-2000 WOOJIN COPOLYMER; Antimony trioxide: S-05N Shanxing Antimony Industry; Polyethylene A: viscosity average molecular weight about 400,000, GUR 2105, Celanese; Polyethylene B: viscosity average molecular weight about 560,000, L0504F, Sinopec; Polyethylene C: viscosity average molecular weight about 140,000, LA0710, Qatar; Ultra-high molecular weight polyethylene: PE-UHMW MI, Sinopec, viscosity-average molecular weight is about 1.57 million; Polyethylene glycol A: weight average molecular weight 500, PEG-500, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol B: weight average molecular weight 4000, PEG-4000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol C: weight average molecular weight 8000, PEG-8000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol D: weight average molecular weight 10000, PEG-10000, Shanghai Haoyuan Biopharmaceutical Technology Co., Ltd.; Polyethylene glycol E: weight average molecular weight 15000, PEG-15000, Shanghai Haoyuan Biotechnology Co., Ltd.

[0032] The flame retardant polyamide material of the embodiment and comparative example is prepared by mixing the components uniformly according to the ratio, putting them into a twin-screw extruder for melt mixing, extruding and granulating to obtain the flame retardant polyamide material; wherein the screw aspect ratio of the twin-screw extruder is 44:1, the barrel temperature is 230-260°C, and the screw speed is 400rpm.

[0033] Various test methods: (1) Resistance to moisture and heat aging: The flame retardant polyamide material was injection molded into a 100*100*1.5mm square plate and stored at 75°C and 75% humidity for 500 hours; then the material's drop ball impact performance was tested. The specific test method is as follows: a 2kg steel ball was used to perform a drop ball impact test at a height of 1.5m at room temperature. The sample cracking levels are as follows: obvious cracking is considered level 3, cracks but no cracks are considered level 2, and no cracks visible to the naked eye are considered level 1.

[0034] (2) Flame retardancy: UL-94 is used to test the flame retardancy level of materials, which is divided into V-0, V-1 and V-2.

[0035] (3) Bending performance after high temperature baking: The prepared material is placed in an injection molding machine at 275°C for 5 minutes, and a 280T injection molding machine is used to mold the specimen at a rated speed of 50% and a pressure of 60 bar. High temperature performance test: Prepare a 100*13*0.8mm sample, dry it at 175°C for 4 hours, take out the sample and bend it at 90°C within 1 minute, repeat N times, and the sample is considered qualified if it does not break after 3 times. The more times, the better.

[0036] Table 1: Content (parts by weight) of each component of flame-retardant polyamide material and test results of Examples 1-7 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 PA66 75 75 75 75 PA6 70 PA10T 75 PA1010 80 Brominated polystyrene A 18 14 22 30 18 18 Brominated polystyrene B 18 Antimony trioxide 7 5 10 12 7 7 7 Polyethylene A 7.5 4.5 9 12 7.5 6 Polyethylene B 7.5 Polyethylene glycol B 2.5 1.5 3 4 2.5 2.2 4 Polyethylene: Polyethylene glycol weight ratio 3 3 3 3 3 3.4 1.5 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 V-0 Impact resistance after heat and humidity aging 1 1 1 1 1 1 2 Heat resistance after bending, second 8 7 7 6 7 5 5 Table 2: Content (parts by weight) of each component of flame-retardant polyamide materials and test results of Examples 8-13 Example 8 Example 9 Example 10 Embodiment 11 Example 12 Embodiment 13 PA66 75 75 75 75 75 75 Brominated polystyrene A 18 18 18 18 18 18 Antimony trioxide 7 7 7 7 7 7 Polyethylene A 7.1 7.8 8.3 7.5 7.5 7.5 Polyethylene glycol B 2.9 2.2 1.7 Polyethylene glycol A 2.5 Polyethylene glycol C 2.5 Polyethylene glycol D 2.5 Polyethylene: Polyethylene glycol weight ratio 2.4 3.5 4.9 3 3 3 Flame retardant V-0 V-0 V-0 V-0 V-0 V-0 Resistance to heat and humidity aging shock 1 1 2 2 1 1 Heat resistance after bending, second 6 6 5 6 8 7 It can be seen from Examples 1 / 7 / 8 / 9 / 10 that the preferred weight ratio of polyethylene to polyethylene glycol has better resistance to wet heat aging.

[0037] It can be seen from Examples 1 / 11 / 12 / 13 that the preferred polyethylene glycol weight average molecular weight has better resistance to moist heat aging.

[0038] Table 3: Content of each component (parts by weight) and test results of flame retardant polyamide materials in comparative examples 1-6 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 PA66 75 75 75 75 75 75 Brominated polystyrene A 18 18 18 18 18 Brominated polystyrene C 18 Antimony trioxide 7 7 7 7 7 7 Polyethylene A 7.5 7.5 5 9 Polyethylene C 7.5 Ultra high molecular weight polyethylene 7.5 Polyethylene glycol B 2.5 2.5 2.5 5 1 Polyethylene glycol E 2.5 Polyethylene: Polyethylene glycol weight ratio 3 3 3 3 1 9 Flame retardant V-2 V-2 V-2 V-2 V-2 V-2 Resistance to heat and humidity aging shock 3 3 3 3 3 3 Heat resistance after bending, second 1 2 1 2 2 1 It can be seen from Comparative Example 1 that if the molecular weight of brominated polystyrene is too low, not only is the flame retardancy insufficient, but also due to its low molecular weight it is difficult to coordinate with the molecular weight of polyethylene, resulting in poor resistance to wet heat aging and reduced flame retardancy.

[0039] It can be seen from Comparative Example 2 that polyethylene with too low viscosity average molecular weight has poor bending performance, so the bending performance of the flame-retardant polyamide material used in the present invention is insufficient, and the flame retardancy and moisture-heat aging resistance are also reduced due to unknown factors.

[0040] It can be seen from Comparative Example 3 that if the viscosity-average molecular weight of polyethylene is too high, its compatibility with brominated polystyrene is poor, resulting in poor resistance to wet heat aging and reduced flame retardancy.

[0041] It can be seen from Comparative Example 4 that if the weight average molecular weight of polyethylene glycol is too low, it will also lead to poor resistance to moist heat aging and reduce flame retardancy.

[0042] It can be seen from Comparative Examples 5-6 that if the ratio of polyethylene / polyethylene glycol is not within the scope of the present invention, the moisture and heat aging resistance and flame retardancy are poor.

[0043] Table 4: Content of each component (parts by weight) and test results of flame retardant polyamide materials in comparative examples 7-9 Comparative Example 7 Comparative Example 8 Comparative Example 9 PA66 75 75 75 Decabromodiphenylethane 18 Epoxy Bromide 18 Brominated polystyrene D 18 Antimony trioxide 7 7 7 Polyethylene A 7.5 7.5 7.5 Polyethylene glycol B 2.5 2.5 2.5 Polyethylene: Polyethylene glycol weight ratio 3 3 3 Flame retardant V-0 V-2 V-1 Resistance to heat and humidity aging shock 3 3 3 Heat resistance after bending, second 1 1 1 It can be seen from Comparative Example 7 that when decabromodiphenylethane is used, V-0 flame retardancy can be obtained due to its high bromine content, but the heat resistance / wet heat aging resistance is poor.

[0044] It can be seen from Comparative Example 8 that when brominated epoxy is used as a flame retardant, the compatibility with the system is poor and the overall performance is poor.

[0045] It can be seen from Comparative Example 9 that when the molecular weight of brominated polystyrene is too high, its dispersibility in the system is poor, V-0 flame retardancy cannot be obtained, and the heat resistance / wet heat aging resistance is poor.

Claims

1. A flame retardant polyamide material, characterized in that: By weight, it includes the following components: Polyamide 70-80 parts; 12-30 parts of brominated polystyrene; Contains 5-12 parts of antimony flame retardant synergist; Compound heat resistant agent 6-16 parts; The composite heat-resistant agent is a composite of polyethylene and polyethylene glycol, and the weight ratio of polyethylene to polyethylene glycol is (1.5-5):1; The viscosity average molecular weight of the polyethylene is 400,000-750,000; The weight average molecular weight of the polyethylene glycol is 450-12000; The weight average molecular weight of the brominated polystyrene is 180,000-250,000.

2. The flame retardant polyamide material according to claim 1, characterized in that The weight ratio of polyethylene:polyethylene glycol is (2.4-3.5):

1.

3. The flame retardant polyamide material according to claim 1, characterized in that The antimony-containing flame retardant synergist is selected from at least one of antimony trioxide and antimony pentoxide.

4. The polyamide material according to claim 1, characterized in that The weight average molecular weight of the polyethylene glycol is 3800-11000.

5. The flame retardant polyamide material according to claim 1, characterized in that The polyamide resin is selected from at least one of aliphatic polyamide resin, semi-aromatic polyamide resin and polylactamide resin.

6. The flame retardant polyamide material according to claim 1, characterized in that: The invention also comprises 0-5 parts of auxiliary agents by weight, wherein the auxiliary agents are selected from at least one of lubricants, nucleating agents and antistatic agents.

7. The method for preparing the flame retardant polyamide material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing the components according to a ratio, putting the components into a twin-screw extruder for melt mixing, extruding and granulating, and obtaining a flame-retardant polyamide material; wherein the screw length-diameter ratio of the twin-screw extruder is 40-48:1, the barrel temperature is 230-260°C, and the screw speed is 200-550rpm.

8. Use of the flame retardant polyamide material according to any one of claims 1 to 6, characterized in that: Used to prepare electronic equipment casings.

Citation Information

Patent Citations

  • Super-tough super-low-temperature-resistant super-wear-resistant flexible nylon alloy material and preparation method thereof

    CN112430391A

  • Polyamide composite material capable of being subjected to gas-assisted molding

    CN112552676A

  • High-temperature-resisting xanthochroia-resisting high-performance flame retarding PET (Polyethylene Terephthalate) composite material and preparation method thereof

    CN103059525A

  • Weather-proof ABS / PA6 material for flame retardation extrusion technology and preparation method thereof

    CN104119634A

  • Brominated flame-retardant polyamide composite material as well as preparation method and application thereof

    CN116102881A